Slovenska kratka pripovedna proza po letu 1980 - Žbogar, Alenka (Slavistična revija, 2009)
The article sheds light on changes in Slovene short fiction after 1980 and explains why they have been occuring, using quantitative, structural, and content analysis of Slovene short fiction at the thur of the millennium. The author also examines whether erotic love in the postmodern type of Slovene short fiction after 1980 presents itself as a miniature, regardless of the generation of the author in question.
Keywords: 1980-2008; fabulation; kratka pripovedna proza; kratka proza; post-modernism; postmodernizem; short fiction; short story; Slovene literature; slovenska književnost; zgodbarstvo